Swot Analysis Of Implementation Of Mutlaqoh Muḍarabah Contract On Pension Saving Products At Indonesian Sharia Bank Kc Bojonegoro - Muhammad Muslih; Agus Wahyu Irawan; Kholishudin; Shelvyna Rikantasari (Enrichment : Journal of Management, 2022)
This study aims to explain the implementation of muḍarabah mutlaqoh contracts in retirement savings at Bank Syariah Indonesia KCP Bojonegoro. This study uses a qualitative research type using SWOT analysis. By using the method of collecting data through interviews, observation and documentation of the subject. Basically, the activities of every Islamic bank are not much different from conventional banks. Islamic banks have an intermediary function, namely bridging the interests of people who need funds with those who have excess funds. In addition, Islamic banks also have a mandate function so that they are obliged to be responsible and maintain the security of the funds stored. In accordance with sharia principles in the National Sharia Council Fatwa No. 02/DSN-MUI.IV/2000 concerning savings which are divided into two types, namely savings that use the wadi'ah principle and the principle of muḍarabah mutlaqoh. The results of this study indicate that this retirement savings uses a muḍarabah mutlaqoh contract in which this contract uses the principle of profit sharing between shahibul mall (customers) and muḍarib (managers) with the distribution using the profit sharing method or the net revenue sharing method between both parties based on the agreed ratio. The implementation of retirement savings includes: requirements to become a prospective customer, opening savings to closing savings, profit sharing for retirement savings and product promotions. The obstacles that exist in retirement savings are: lack of public trust and must have two savings.